The legal consequences of breach of performance in cooperation between service providers and companies that use event organizers (PT. Showbitz Mitra Utama) - Sihotang, Putri Yunita; Nasution, Alvin Hamzah (Privietlab, 2025)
This study aims to analyze the legal consequences of default in the cooperation agreement between service providers and companies that use Event Organizer services, especially at PT Showbitz Mitra Utama. The formulation of the problems raised in this study includes: (1) the implementation of the cooperation agreement between the provider and the user of Event Organizer services, (2) the legal consequences of default arising in the cooperation agreement, and (3) dispute resolution carried out by the parties in resolving the default that occurred. This study uses a qualitative approach with a case study on PT Showbitz Mitra Utama, which is involved in a cooperative relationship with the Event Organizer service user company. The results show that the cooperation agreement between the two parties is generally regulated in the form of a written contract that includes the obligations and rights of each party. Default occurs when one party fails to fulfill the performance in accordance with the agreed provisions, which results in the obligation of compensation and dispute resolution through negotiation, mediation, or legal channels. Dispute resolution can be carried out with peaceful efforts between the two parties; however, if it fails, legal proceedings through the courts become the last resort. This research contributes to the understanding of the importance of written agreements and dispute resolution mechanisms in reducing the negative impact of defaults in relationships.